Sistem Pendukung Keputusan untuk Menentukan Peminatan Mahasiswa Menggunakan Metode Fuzzy Tsukamoto dan TOPSIS - Juan Keinan thimothi Paparang; Magdalena A. Ineke Pakereng (Universitas Nusa Cendana, 2026)
This study aims to design a decision support system that helps students choose a specialization that suits their abilities and interests, thus supporting timely graduation. The method used is a combination of Fuzzy and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution). This study was conducted to obtain the most appropriate specialization recommendations for students, based on existing criteria. The criteria used in this study include academic scores of compulsory courses relevant to each specialization, skills, and programming abilities. The results of the study will provide specialization recommendations that are sorted by the highest preference value, so that students can see the choices of specializations that best suit their abilities and interests. In addition, these results are also expected to help students make the right decisions, as well as increase their chances of graduating on time.